Comparison between the results of the rulers of second-and third-degree fitness tests football - Qasim, sabah; Ali, Mohsen (Journal of Physical Education, 2012)
The study aimed to compare the results of the rulers of the second degree and third degree physical fitness tests and the differences for the distances traveled during times of testing and number (20) and second degree rule (20) third-degree rule for football. The conclusions are not giving enough rest between tests of fitness for referees, which have negatively impacted on the results of tests sprint the third degree, fifth and sixth sessions of the third degree as well as double the speed when the rulers of the third degree.